Separation and identification of lipids in the photosynthetic cousins of Apicomplexa Chromera velia and Vitrella brassicaformis. Issue 17 (14th August 2017) - Tomčala, Aleš; Kyselová, Veronika; Schneedorferová, Ivana; Opekarová, Iva; Moos, Martin; Urajová, Petra; Kručinská, Jitka; Oborník, Miroslav
Abstract: The alveolate algae Chromera velia and Vitrella brassicaformis (chromerids) are the closest known phototrophic relatives to apicomplexan parasites. Apicomplexans are responsible for fatal diseases of humans and animals and severe economic losses. Availability of the genome sequences of chromerids together with easy and rapid culturing of C. velia makes this alga a suitable model for investigating elementary biochemical principals potentially important for the apicomplexan pathogenicity. Such knowledge allows us to better understand processes during the evolutionary transition from a phototrophy to the parasitism in Apicomplexa. We explored lipidomes of both algae using high‐performance liquid chromatography with mass spectrometry or gas chromatography with flame ionization detection. A single high‐performance liquid chromatography with mass spectrometry analysis in both ionization modes was sufficient for the separation and semi‐quantification of lipids in chromerid algae. We detected more than 250 analytes belonging to five structural lipid classes, two lipid classes of precursors and intermediates, and triacylglycerols as storage lipids. Identification of suggested structures was confirmed by high‐resolution mass spectrometry with an Orbitrap mass analyzer. An outstandingly high accumulation of storage triacylglycerols was found in both species. All the investigated aspects make C. velia a prospective organism for further applications in biotechnology.